ETHNIC HETEROGENEITY IN THE MALAYSIAN ECONOMY - Shafii, Zuhrina (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2009)
The purpose of this article is to outline the current state of knowledge in relation of economic involvement and ethnicity in Malaysia. Firstly, this chapter will review on the state of employment in relation to the ethnic groups in Malaysia. This is important since the income factor is one of the major factors that determine the level of economic participation and the state of wealth of individuals. Stable and adequate level of income is one of the determinants of wealth accumulation for individuals other than wealth and net wealth level. This raises the question of employment opportunities among different ethnic groups in Malaysia. The root of the employment opportunities, it can be argued, stems from the access of different ethnic groups to high education, which also discussed in the article.